Regulating Intratumoral Fungi With Hydrogels: A Novel Approach to Modulating the Tumor Microbiome for Cancer Therapy - Ping Chen; Weiwei Tian; Anqi Zeng; Huan Gu; Jin Zeng (Cancer Medicine, 2025)
ABSTRACT Background Fungi in tumors act as a double‐edged sword, potentially worsening or alleviating malignancy based on the ecological balance within the tumor microenvironment (TME). Hydrogels, as innovative drug delivery systems, are poised to redefine treatment paradigms. As advanced biomaterials, they offer a versatile platform for encapsulating and releasing antifungal agents and immunomodulators, responding to the TME's unique demands. Methods We have conducted and collated numerous relevant reviews and studies in recent years from three aspects: Hydrogels, intra‐tumoral fungi, and tumor microbe microenvironment, in the hope of identifying the connections between hydrogels and intra‐tumoral microbes. Results This review underscores the crucial role of intra‐tumoral microbes, particularly fungi, in tumorigenesis, progression, and treatment efficacy. At the same time, we concentrated on the findings of hydrogels investigations, with their remarkable adaptability to the tumor microenvironment emerge as intelligent drug delivery systems. Conclusions Hydrogels unique ability to precisely target and modulate the tumor microflora, including fungi, endows them with a significant edge in enhancing treatment efficacy. This innovative approach not only holds great promise for improving cancer therapy outcomes but also paves the way for developing novel strategies to control metastasis and prevent cancer recurrence.